Effect of Amount and Size of Quartz on Mechanical and Dielectric Properties of Electrical Porcelain. Issue 3 (3rd July 2018) - Boussouf, Lila; Zehani, Fouzia; Khenioui, Youcef; Boutaoui, Noureddine
ABSTRACT: The present work reports a systematic study on the influence of particle size and amount of quartz on mechanical and dielectric properties of electrical porcelain. The samples of electrical porcelain were elaborated using quartz, kaolin, clay, feldspar and zircon. The quartz was milled at 20, 30 and 45 h. Phase and microstructure evolution of the samples synthesized were characterized by X-ray diffraction, differential thermal analysis and scanning electron microscopy. The investigation revealed the formation of mullite, unsolved quartz and creation of microcracks and pores. Mechanical and dielectric strength measurements were performed on the samples sintered at 900 o, 1000 o, 1100 o and 1275 o C. The mechanical strength increased from 578.97 to 842.49 kg.cm –2 and the dielectric strength increased from 26.34 to 28.28, 28.77 to 32.24 and 30.32 to 36.27 kV.mm –1 for different milled times. The properties of electrical porcelain were attributed to the particle size of quartz. GRAPHICAL ABSTRACT: